2016
DOI: 10.18632/oncotarget.11556
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 1 is a novel regulator of MYCN in neuroblastoma

Abstract: Amplification or overexpression of MYCN is associated with poor prognosis of human neuroblastoma. We have recently defined a MYCN-dependent transcriptional signature, including protein arginine methyltransferase 1 (PRMT1), which identifies a subgroup of patients with high-risk disease. Here we provide several lines of evidence demonstrating PRMT1 as a novel regulator of MYCN and implicating PRMT1 as a potential therapeutic target in neuroblastoma pathogenesis. First, we observed a strong correlation between MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…In human melanoma, Li, et al reported that PRMT1 is overexpressed in human melanoma and may regulate tumour growth and metastasis via targeting ALCAM [8]. Eberhardt, et al indicated that PRMT1 is a novel regulator of MYCN, which implicates PRMT1 as a potential therapeutic target in neuroblastoma pathogenesis [28]. These reports might also support the correlation between PRMT1 and HCC progression, specifically tumour growth and metastasis, which was shown in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In human melanoma, Li, et al reported that PRMT1 is overexpressed in human melanoma and may regulate tumour growth and metastasis via targeting ALCAM [8]. Eberhardt, et al indicated that PRMT1 is a novel regulator of MYCN, which implicates PRMT1 as a potential therapeutic target in neuroblastoma pathogenesis [28]. These reports might also support the correlation between PRMT1 and HCC progression, specifically tumour growth and metastasis, which was shown in this study.…”
Section: Discussionsupporting
confidence: 82%
“…PRMT1 also regulates other transcription factors that are involved in regulation of cell‐cycle progression and proliferation, such as FOXOs, p53, c‐Myc, as well as upstream signaling molecules involved in proliferation, epidermal growth factor receptor . We analyzed PRMT1 KO mouse gene expression and used IPA analysis to find the main upstream regulators affected by PRMT1.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is an important transcription factor in regulating myeloid cell functions (8 -10). Previous studies on c-Myc and N-Myc regulation by PRMT1 suggest that PRMT1 regulates Myc gene expression (20,21) and function (21).…”
Section: Arginine Methylation Is Required For C-myc-p300 Interactionmentioning
confidence: 93%